Short-course PD-1 blockade in locally advanced nasopharyngeal carcinoma: a phase II randomized trial protocol (Tori-013) - Jia, Hongyuan; Wang, Junchao; Zhang, Ling; Li, Haijun; Du, Yalei; Luo, Wenjuan; Wei, Zou; Wang, Xiaohui; Wang, Weidong (Frontiers in Immunology, 2025)
While immunotherapy has demonstrated encouraging efficacy in locally advanced nasopharyngeal carcinoma (LANPC), the optimal combination modalities and treatment duration remain undetermined. In the present study, we developed a clinical trial protocol to evaluate shortened period of immunotherapy could enhance the efficacy of LANPC. This open-label, randomized, single-blind, multicenter phase II trial (Tori-013) investigates the efficacy and safety of toripalimab (anti-PD-1 monoclonal antibody) combined with induction chemotherapy (IC) followed by concurrent chemoradiotherapy (CCRT) in patients with stage III/IVa nasopharyngeal carcinoma (NPC). Eligible participants (estimated n=154) are randomized 1:1 to receive either IC (gemcitabine + cisplatin) plus CCRT (cisplatin + radiotherapy ≥ 70 Gy) with toripalimab (240 mg, Q3W) or placebo. Toripalimab/placebo is administered during IC and CCRT phases, followed by two additional cycles post-radiotherapy. The primary endpoint is 3-year progression-free survival (PFS), with secondary endpoints including overall survival (OS), objective response rate (ORR), Epstein-Barr virus (EBV) DNA dynamics, lymphocyte subset changes, and safety. Safety assessments focus on immune-related adverse events (irAEs) graded by CTCAE v5.0. Approved by the Ethics Committee of Sichuan Cancer Hospital (KY-2021-113) and registered (ChiCTR2200055494), this trial aims to establish a novel, streamlined immunochemoradiotherapy strategy for locally advanced NPC, potentially enhancing efficacy while maintaining tolerability